Effect of ultrasound-advanced oxidation processes for pretreatment of oil palm mesocarp fiber for cellulose extraction - Anggoro, Didi Dwi; Prasetyaningrum, Aji; Udaibah, Wirda; Imtinan, Alifa Bakhitah; Nabilah, Farhanah; Le Monde, Brilliant Umara (International Journal of Renewable Energy Development, 2024)
Palm mesocarp fiber, a by-product of the palm oil industry, holds significant potential as a cellulose source for biofuel, biopolymer, and biocomposite production. However, its utilization is hampered due to the presence of lignin, which covers the cellulose. The use of ozone promotes a high level of lignin degradation, making it efficient in breaking down lignin bonds in lignocellulose. However, the ozonation method has low ozone mass transfer. This deficiency can be overcome with ultrasonic waves because of the cavitation phenomenon that can expand the contact surface of ozone and lignocellulose. The ozonation-ultrasonic hybrid method is used to remove lignin. This research investigates the use of a hybrid ozonation-ultrasonic method with the effect of reaction time and pH under acidic conditions on the pretreatment of palm oil mesocarp fiber. This process was carried out at reaction times (70, 80, and 90 minutes) and solution pH (4, 5, and 6) with an ozone flow rate of 2 L min-1. The cellulose content was analyzed using the Chesson method. The results showed a decrease in lignin and an increase in cellulose, which was confirmed by Fourier Transform Infrared Spectroscopy (FTIR) analysis shows a decrease in the lignin absorption peak at 1635 cm-1 and 1420 cm-1. XRD analysis showed an increase in crystallinity after pretreatment, with lignin degradation observed at 6.35%. SEM Morphological showed a more friable, stable, and porous surface after pretreatment, indicating the presence of perforations in the cell walls and the damage to the lignin structure. Therefore, this research succeeded in reducing the use of chemicals in the biomass waste delignification process. The ozonation-ultrasonic hybrid pretreatment process, which aims to degrade lignin in palm fiber biomass, shows promising results, producing high cellulose content in palm fiber by reducing the amount of chemicals as mostly used in conventional processes.